The application of Signalling Theory to health-related trust problems: The example of herbal clinics in Ghana and Tanzania. (September 2017) - Hampshire, Kate; Hamill, Heather; Mariwah, Simon; Mwanga, Joseph; Amoako-Sakyi, Daniel
Abstract: In contexts where healthcare regulation is weak and levels of uncertainty high, how do patients decide whom and what to trust? In this paper, we explore the potential for using Signalling Theory (ST, a form of Behavioural Game Theory) to investigate health-related trust problems under conditions of uncertainty, using the empirical example of 'herbal clinics' in Ghana and Tanzania. Qualitative, ethnographic fieldwork was conducted over an eight-month period (2015–2016) in eight herbal clinics in Ghana and ten in Tanzania, including semi-structured interviews with herbalists (N = 18) and patients (N = 68), plus detailed ethnographic observations and twenty additional key informant interviews. The data were used to explore four ST-derived predictions, relating to herbalists' strategic communication ('signalling') of their trustworthiness to patients, and patients' interpretation of those signals. Signalling Theory is shown to provide a useful analytical framework, allowing us to go beyond the primary trust problem addressed by other researchers – cataloguing observable indicators of trustworthiness – and providing tools for tackling the trickier secondary trust problem, where the trustworthiness of those indicators must be ascertained. Signalling Theory also enables a basis for comparative work between different empirical contexts that share the underlying condition of uncertainty. Highlights: Applies Signalling Theory (ST) to patient-herbalist trust in Ghana & Tanzania. Herbalists communicate trustworthiness to patients via observable 'signals'. Patients interpret signal reliability based on perceived costs and pay-offs. In conditions of uncertainty, informational mismatches result in misplaced trust. ST allows us to go beyond description, enabling prediction and comparative work.